Pleiotropic effects of miR-183~96~182 converge to regulate cell survival, proliferation and migration in medulloblastoma - Weeraratne, Shyamal Dilhan; Remke, Marc; Pfister, Stefan (Acta neuropathologica, 2012)
Medulloblastomas are the most common malignant brain tumors in children. Several large-scale genomic studies have detailed their heterogeneity, defining multiple subtypes with unique molecular profiles and clinical behavior. Increased expression of the miR-183~96~182 cluster of microRNAs has been noted in several subgroups, including the most clinically aggressive subgroup associated with genetic amplification of MYC. To understand the contribution of miR-183~96~182 to the pathogenesis of this aggressive subtype of medulloblastoma, we analyzed global gene expression and proteomic changes that occur upon modulation of miRNAs in this cluster individually and as a group in MYC-amplified medulloblastoma cells. Knockdown of the full miR-183~96~182 cluster results in enrichment of genes associated with apoptosis and dysregulation of the PI3K/AKT/mTOR signaling axis. Conversely, there is a relative enrichment of pathways associated with migration, metastasis and epithelial to mesenchymal transition, as well as pathways associated with dysfunction of DNA repair in cells with preserved miR-183 cluster expression. Immunocytochemistry and FACS analysis confirm induction of apoptosis upon knockdown of the miR-183 cluster. Importantly, cell-based migration and invasion assays verify the positive regulation of cell motility/migration by the miR-183 cluster, which is largely mediated by miR-182. We show that the effects on cell migration induced by the miR-183 cluster are coupled to the PI3K/AKT/mTOR pathway through differential regulation of AKT1 and AKT2 isoforms. Furthermore, we show that rapamycin inhibits cell motility/migration in medulloblastoma cells and phenocopies miR-183 cluster knockdown. Thus, the miR-183 cluster regulates multiple biological programs that converge to support the maintenance and metastatic potential of medulloblastoma.